Democracy and Citizenship in Scandinavia - Anderson, J. author. aut Link
XX, 308 p.
Keywords: Major changes in citizenship and democracy have taken place in Scandinavia within the last two decades. Participation in conventional forms of politics has declined markedly, and the ability of institutions such as political parties and trade unions to deliver social mobility is being eroded. Instead, Scandinavians are turning towards single issue participation and 'small democracy' in the workplace or in public sector service institutions. The scenario is that of a 'spectator democracy' with engaged and conscious spectators who lack the long-term political commitment to engage actively in 'big democracy'. Also, Scandinavian citizenship is challenged by structural unemployment, EU membership, and immigration. This book deals with the details of these processes and in particular how they have affected political participation, identity and social polarization.